The Hong Kong Jockey Club: Driving Sustainability and Riding High Together – A Case Study - Yao, Yihong; Li, Dongya (European Journal of Sustainable Development, 2016)
In recent years, sustainability has become a popular topic for both business and society. There is little dispute that companies and organizations have increasingly paid attention to social and environmental issues, and thus sustainability has come under the spotlight. However, The Hong Kong Jockey Club (“HKJC” or “the Club”), the largest single taxpayer and non-government charitable donor in Hong Kong, has been paying attention to environmental and social issues for decades although its “sustainability efforts” were not given a label for most of that period. The year of 2009 was a milestone of the HKJC’s sustainability endeavors as in this year the HKJC formed its first Sustainability Committee, raising sustainability to the strategic level within the Club. The first sustainability report of HKJC was released in 2011, making the HKJC’s dialogue with the community, also within the Club, transparent. In 2014, the Club introduced Supplier Sustainability Guidelines, aiming to increase the sustainability standards of the Club’s business partners, and in turn, of all local businesses. This case depicts how HKJC achieved sustainability through its endeavors in the environmental, social, and governance (ESG) areas, thus contributing to the community and enabling a better future for its stakeholders and for society as a whole. This case also discusses the evolution of the HKJC’s sustainability governance structure and strategy, the progress of HKJC’s sustainability practices from 2009 to 2016, and HKJC’s sustainability challenges. Keywords: Hong Kong Jockey Club, sustainability governance, sustainability practice, sustainability innovation, carbon footprint, supplier sustainability, stakeholder engagement, case study